If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13y + -6 = 3y + -6 + -6 Reorder the terms: -6 + 13y = 3y + -6 + -6 Reorder the terms: -6 + 13y = -6 + -6 + 3y Combine like terms: -6 + -6 = -12 -6 + 13y = -12 + 3y Solving -6 + 13y = -12 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. -6 + 13y + -3y = -12 + 3y + -3y Combine like terms: 13y + -3y = 10y -6 + 10y = -12 + 3y + -3y Combine like terms: 3y + -3y = 0 -6 + 10y = -12 + 0 -6 + 10y = -12 Add '6' to each side of the equation. -6 + 6 + 10y = -12 + 6 Combine like terms: -6 + 6 = 0 0 + 10y = -12 + 6 10y = -12 + 6 Combine like terms: -12 + 6 = -6 10y = -6 Divide each side by '10'. y = -0.6 Simplifying y = -0.6
| 3.4+10m=7.93 | | 15287ft=2.9mi | | x-6*2x=24 | | -2y+4=-14+8y | | -7x-32=x+13 | | -3(3y-7)-y=-3(y-5) | | 8.48x-2.6=-7.17x-7.1 | | h=55-20t-5t^2 | | -2y-7=15 | | 3/4(x-4)=2(x-1) | | -10v-10=9v-8 | | .25(n+2)=1 | | .40+.30(25-x)=.35(25) | | 8x-4x+2=x-4+6 | | 0.4(2c-30)=-0.8(c-4) | | x-6*2=24 | | (X+y+3z)-(4x-6y+z)= | | 90=w+w+(4w-6) | | 0.2(6c-48)=-0.6(c-2) | | 6y+2-y=8+4y-7 | | 2(n)=6-20 | | (2a+1)-a+2= | | 2t=5w-y | | -5x/520 | | 2t=5t-y | | 90=x+x-2 | | (X+y+4z)-(2x-6y+z)= | | 180=x+x+(x+3) | | 3/5m-5-1/2=1 | | 5/11a-3=16/11 | | 3/5m-5_1/2m=1 | | -2(x-7)=2(1+5x) |